ECONOMIC MELTDOWN AND INSECURITY: RETHINKING THE ROLE OF SCIENCE IN NATION BUILDING (UNIZIK Journal of STM Education, 2025)
The ongoing convergence of economic collapse and insecurity present a serious threat to nation building in low and middle income contexts and together, economic collapse (characterized by issues like inflation, fiscal deficits and unemployment) combined with expanding insecurity (the existence of terrorism, communal violence and organized crime) create a feedback loop that destabilizes development. Traditional modes of engagement like foreign aid or political reform are often too inaccurate, lack innovative disruptions, and require foresight, future-looking prospects but fails to recognize the importance of science and innovation, specifically in the design of sustainable and systemic solutions. This article rethinks science as an agent for change in national development. We argue that science, which in this case extends to research, technology, innovation, and evidence-based provision, needs to be repositioned at the centre of economic recovery and security reform moving forward. This study showcases how deliberate investments enhances scientific research, STEM education, data-based policymaking, and technology infrastructure can lead to renewed economic recovery, improved national security, and rebuilding public confidence. Ultimately, the article supports the purposeful infusion of science into governance, policy and society, and moving it from the background to the forefront of progress. Faced with impending economic collapse and rising threats, science is no longer an option, it is the catalyst for re-birth.
Keywords: Economic meltdown, Insecurity, Science, Re-think, Nation building